4 Enhanced dissemination of evidence syntheses to support emerging new models of care. Issue Volume 23:Issue Supplement 1(2018) (June 2018) - Ronquillo, Charlene; Turner, Alison; Baxter, Susan; Bunn, Frances; Sheaff, Rod; Pearson, Mark; Wilson, Paul; Hanratty, Barbara
Abstract : Objectives: This case study describes a programme of knowledge translation and mobilisation activities aimed to enhance the dissemination of five recent evidence syntheses to support emerging new models of care across England. The work aims to synthesize and articulate practical insights to prompt stakeholders to apply evidence from these studies to local NHS transformation programmes and decisions. The programme of activities was designed to enable the evidence to be spread widely (reaching decision makers, practitioners and public representatives across the health and care system) and in-depth (helping teams to act on our findings). We describe our approaches for targeting a diverse group of stakeholders, including NHS leaders developing Sustainability and Transformation Partnerships (STPs) and/or Accountable Care Systems (ACS) to improve coordination across different health services, and better coordinate these with social care, to maintain the quality and reduce the cost of all these services in aggregate. Method: Our aim was to combine critically reviewed evidence with practical experience of service improvement and transformation. A comprehensive synthesis of the literature 1 on knowledge mobilisation informed our approach to summarising the results across evidence syntheses, developing materials, communication, and disseminating these materials and key messages to stakeholders. The focus on increasing the impact of the evidence in the original studies upon health and health care guided the development and dissemination of communications materials. We leveraged team members' and collaborators' established networks and expertise in translating evidence into useable tools to support service improvement, stakeholder engagement in service redesign, and liaison across teams and stakeholder groups. We used an evaluation questionnaire to collect formative evidence about the impact of the dissemination, and about stakeholders' perspectives and experiences of engaging with the project outputs. From this formative evaluation, we summarised practical recommendations for disseminating evidence generated by future research projects. Results: This case study illustrated an approach to mobilising knowledge from different evidence syntheses with the view, from the outset, of maximising the impact of the evidence and of ensuring that research outputs are developed and disseminated ways that target the various stakeholders' needs and interests. We encountered certain differences in the ways needed to disseminate research outputs to diverse groups of stakeholders with varying needs. The use of team members' existing channels and networks among the relevant organisations increase the reach of the disseminated material and presented opportunities to identify alignment with these network' existing priorities and engagement activities. Team members' combined academic and practice-based expertise proved crucial in lending credibility and access to key influencers and target audiences. Conclusions: This case study presents a programme of evidence-informed knowledge translation and mobilisation, underpinned with pragmatic leveraging of researchers' existing networks and relationships established during each respective project. Our formative evaluation and critical reflections on mobilising complex knowledge to inform the design and implementation of New Models of Care in the NHS has important lessons for accelerating the use of evidence to inform decisions about health and social care service design. Reference: Davies H, et al. Mobilising knowledge to improve UK healthcare: Learning from other countries and other sectors – a multimethod mapping study. Health Services and Delivery Research 2015;3.